2017
DOI: 10.1093/ckj/sfx078
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in membrane cofactor protein (CD46) gene in Indian children with hemolytic uremic syndrome

Abstract: BackgroundMutations in the CD46 gene account for an important proportion of patients with atypical hemolytic uremic syndrome (aHUS) who characteristically show multiple relapses, no response to plasma exchange and low recurrence risk in allograft. We screened for mutations in CD46 in patients with and without circulating anti-factor H (FH) antibodies–associated aHUS.MethodsWe estimated CD46 surface expression by flow cytometry and sequenced the CD46 gene in 23 and 56 patients with and without circulating anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(48 reference statements)
1
7
1
Order By: Relevance
“…This gene encodes a protein with cofactor activity for the inactivation of complement components C3b and C4b. Based on in vitro studies and clinical evidence, this mutation is assumed to play a pathogenic role in the development of aHUS [ 6 ], (b) heterozygous for a rare variation (c.463A > C) causing an amino acid change (p.K155Q) in the complement C3 protein. This variation had a role in the development of aHUS and another form of thrombotic microangiopathy [ 7 , 8 ], (c) homozygous for the CFH H3 haplotype (with the rare alleles c.-331C > T, Q672Q and E936D polymorphisms), which has been reported as a risk factor for aHUS [ 9 ], (d) homozygous for the MCPggaac haplotype of the CD46 gene, which has been reported as a risk factor for the development of aHUS [ 10 ].…”
Section: Clinical Casementioning
confidence: 99%
“…This gene encodes a protein with cofactor activity for the inactivation of complement components C3b and C4b. Based on in vitro studies and clinical evidence, this mutation is assumed to play a pathogenic role in the development of aHUS [ 6 ], (b) heterozygous for a rare variation (c.463A > C) causing an amino acid change (p.K155Q) in the complement C3 protein. This variation had a role in the development of aHUS and another form of thrombotic microangiopathy [ 7 , 8 ], (c) homozygous for the CFH H3 haplotype (with the rare alleles c.-331C > T, Q672Q and E936D polymorphisms), which has been reported as a risk factor for aHUS [ 9 ], (d) homozygous for the MCPggaac haplotype of the CD46 gene, which has been reported as a risk factor for the development of aHUS [ 10 ].…”
Section: Clinical Casementioning
confidence: 99%
“…In one case, the variant caused deletion of 155 base pairs at the 3′ of exon 2 (deleting 48 amino acids in CCP1) [ 42 ], while another study found it produced an mRNA causing a frame-shift mutation resulting in CD46 truncation in CCP2 (E97Kfs*33) [ 45 ]. The IVS2 + 2T > G variant was the most prevalent mutation (and a ‘hot spot’) in a cohort of aHUS-afflicted Indian children [ 46 ]. Further, it was also the most prevalent mutation (13/485) in an international aHUS cohort analyzed by Piras et al [ 41 ].…”
Section: Deficiency Statesmentioning
confidence: 99%
“…Mutations affecting the regulatory proteins Factor H, Factor I, or CD46 (Membrane Cofactor Protein) and Factor B lead to severe dysregulation of the alternative pathway resulting in atypical hemolytic uremic syndrome (aHUS) and membranoproliferative glomerulonephritis (MPGN). Flow cytometry analysis for CD46 on neutrophils is a useful screening tool for the diagnosis of aHUS in combination with evaluation of complement regulatory proteins …”
Section: Group Viii: Complement Deficienciesmentioning
confidence: 99%